Process evaluation of the implementation of the assessment of burden of chronic conditions tool in Dutch primary care - lessons from a qualitative implementation study - Danny Claessens; Marcia Vervloet; Esther A. Boudewijns; Lotte C.E.M. Keijsers; Annerika H.M. Gidding-Slok; Onno C.P. van Schayck; Bjorn Winkens; Liset van Dijk (BMC, 2024)
Abstract Background The Assessment of Burden of Chronic Conditions (ABCC-)tool is developed to facilitate a personalized approach to care in the patient-healthcare provider (HCP) conversation based on shared decision-making and individualized care plans. An effectiveness study highlighted its effect on the perceived quality of care and patient activation. Successful implementation of novel interventions necessitates an understanding of the user's actual application, user experiences and an evaluation of implementation outcomes. This study aims to evaluate the implementation of the ABCC-tool by HCPs in Dutch primary care. Methods This study is the process evaluation of a larger type 1 effectiveness-implementation hybrid trial. Semi-structured interviews with HCPs, who were interventionists in the hybrid trial, were held at three and twelve months after they started using the ABCC-tool. The Reach-Effectiveness-Adoption-Implementation-Maintenance (RE-AIM) framework was used to evaluate implementation outcomes. The Implementation domain was further strengthened with an evaluation of implementation fidelity using Carroll's framework. Inductive coding and thematic analysis were applied to identify relevant participant experiences and implementation outcomes within the RE-AIM framework. Results Seventeen HCPs (1 general practitioner, 16 practice nurses) participated in the study, representing 39% of potentially eligible participants. Most HCPs applied the tool after finishing their own routines instead of how it is intended to be used, namely from the beginning of the consultation. HCPs reached 2-6 patients. The ABCC-tool was initially adopted, but twelve HCPs stopped using the tool due to COVID-19 related cancellation of consultations. High fidelity was found for applying the questionnaire and visualization. Low fidelity was present for applying shared decision-making, formulating care goals and monitoring progress. HCPs indicated that maintaning the ABCC-tool depended on accompanying training and implementation support. Conclusions HCPs applied the ABCC-tool critically different from intended, potentially diminishing its benefits and ease of use. This evaluation stresses the need for a tailored implementation plan that includes more detailed training and guidance on how and when to use the ABCC-tool.